2011
DOI: 10.1007/s00264-011-1247-1
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of recombinant human bone morphogenic protein-7 and osteogenic differentiation medium on human bone-marrow-derived mesenchymal stem cells in vitro

Abstract: Purpose The purpose of this study was to investigate the effect of recombinant human bone morphogenetic protein-7 (rhBMP-7) with or without osteogenic differentiation medium (ODM) on osteogenic differentiation of primary human bonemarrow-derived mesenchymal stem cells (hBMSCs) in vitro. Method The hBMSCs were isolated from medullary reaming tissue. At 80% confluence, hBMSCs were treated with different concentrations of rhBMP-7 with and without ODM. Alkaline phosphatase (ALP) activity, calcium deposition and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…This proofs previously published in vitro findings. 6 SS and PN decreased more sharply in BM1, RIA0.1, and RIA1 compared to BM0 and RIA0. Overall, hRIA-MSC seemed to react more sensitively to stimulation by BMP-7.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This proofs previously published in vitro findings. 6 SS and PN decreased more sharply in BM1, RIA0.1, and RIA1 compared to BM0 and RIA0. Overall, hRIA-MSC seemed to react more sensitively to stimulation by BMP-7.…”
Section: Discussionmentioning
confidence: 81%
“…Although there is some evidence that BMP-7 stimulates bone formation of hBMSC in vitro, the dose dependent BMP-7 stimulation of hBMSC and hRIA-MSC in vivo is even more interesting and less investigated. 6 Furthermore, the treatment of bone defects is still in need of improvement; a balanced combination of MSC and differentiation factors has not yet been found.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have confirmed that MSCs form bone by differentiating into osteoblasts [7,27,85]. In addition, many other studies have confirmed that the recruitment of factors with an adequate amount of MSCs and the micro-environment around the fracture are effective for fracture repair [71,84,88].…”
Section: Msc Homing Depends On the Conditionsmentioning
confidence: 99%
“…In this study, we built 10 constructs from hMSCs of five different patients and added 1 μg ml −1 BMP-7 for stimulation of bone formation [ 21 ]. We performed mCT acquisition before implantation (T0) and after explantation (T1) and compared the results of both time points.…”
Section: Discussionmentioning
confidence: 99%